Language learner self-evaluations vs. learner goals and their correlation to Foreign Language Anxiety - Hellbom, Saku (My University, 2023)
We asked Finnish English language students to evaluate their own English language proficiencies and their learner goals. The distance between their perceived proficiencies and their learner goals forms a “gap”. Then the students were asked to complete a Foreign Language Classroom Anxiety questionnaire and the results of the questionnaire were then compared to the sizes of the “gap” in an attempt to see whether there was a correlation between the distance between the perceived self-evaluated English language proficiency and their learner goals. There were 20 English students as participants in the original questionnaire, and 10 non-English student participants for the qualitative interviews, which were created to gain supplemental data for analysis. The hypothesis was that those with higher “gap” would experience more from Foreign Language Anxiety and those with lower ones would experience it less. The results showed that while some outliers existed, there were no reliable correlation between the “gap” and Foreign Language Anxiety. What we can gather from the results is that while the “gap” might not have any practical use for studying Foreign Language Anxiety, it is something that hopefully can be elaborated on, as a much more substantial number of participants and further refined methods could give more insight on the possible correlation of Foreign Language Anxiety, perceived self-evaluated English language proficiency and learner goals.
Keywords: Foreign Language Anxiety, Language self-evaluation, Language learner goals